Antimicrobial activity of alexidine, chlorhexidine and cetrimide against Streptococcus mutans biofilm - Ruiz-Linares, Matilde (Ann Clin Microbiol Antimicrob, 2014)
BACKGROUND: The use of antimicrobial solutions has been recommended to disinfect demineralized dentin prior to placing the filling material. The aim of this study was to evaluate the ability of several antimicrobials in controlling Streptococcus mutans (SM) biofilm formed in dentin. METHODS: Antimicrobial activity of 0.2% and 2% chlorhexidine (CHX), 0.2% cetrimide (CTR) and 0.2%, 0.5%, 1% and 2% alexidine (ALX) was assayed on 1-week SM biofilm formed on standardized coronal dentin blocks. Results of SM biofilm antimicrobial activity by different protocols were expressed as the kill percentage of biofilm and the term “eradication” was used to denote the kill of 100% of the bacterial population. To compare the efficacies of the different protocols the Student t test was used, previously subjecting data to the Anscombe transformation. RESULTS: All ALX concentrations tested and 0.2% CTR achieved a kill percentage higher than 99%, followed by 2% CHX with percentages above 96% (no statistically significant difference among them). Whereas 2% ALX and 0.2% CTR respectively showed eradication in 10 and 9 of the twelve specimens, 0.2% CHX did not produce eradication in any case. CONCLUSIONS: The present study shows that, when used for one minute, 2% and 1% alexidine, and 0.2% cetrimide, achieve eradication of Streptococcus mutans biofilm in most specimens when applied to a dentin-volumetric model.